Healing Effects of Saroglitazar Gel in Thermally Induced Burn in Rats - Aram Ibrahim; Hawkar Baiz; Zheen Ahmed; Hemn Othman; Tavga Aziz (Al-Anbar Medical Journal)
Background: Burn is associated with several consequences, including an increased incidence of infection, extended duration of hospitalization, and an increased mortality rate. Both PPARα and PPARβ are shown to play crucial roles in the keratinocyte response to skin damage.Objective: To evaluate the healing effects of saroglitazar (SAR) in thermally induced burns.Materials and Methods: Twenty male adult Wistar rats were allocated into four groups: Negative control, positive control, SAR treated, and silver sulfadiazine (SV) treated groups. The burn was induced thermally in all groups except the negative control, and the treatments started after the induction and continued daily for 21 days. Burn areas were measured on days 0, 7, 14, and 21. On day 21, the animals were euthanized and the blood samples were used to measure the complete blood count, hs-CRP, tumor necrosis factor-α (TNF-α), VCAM-1, and interleukin-10 (IL-10). Burned areas were sent for histopathological analysis.Results: The burned areas significantly decreased after 14 days of treatment with SAR, and more significant attenuations occurred after 21 days, along with decreased VCAM level and significant attenuation of hs-CRP and TNF-α and nonsignificant elevation of IL-10. The histopathological findings support the biochemical findings and show remarkable improvements in skin regeneration and lesion scoring.Conclusion SAR has shown a notable burn-healing effect comparable to that of SV which could be attributed to its anti-inflammatory effects. This finding suggests SAR a candidate to be tested in a clinical setting.